Disappearance of aligning properties of deposited SiOx films as caused by external factors - Kolomzarov, Yu.; Oleksenko, P.; Sorokin, V.; Tytarenko, P.; Zelinskyy, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Thermal and degradation stability of SiOx aligning films deposited by cathode reactive sputtering (CRS) in glow discharge plasma were investigated. It was shown that a heat treatment and other external factors initiate transformations on the surface of aligning film and provided new conditions at the interface. This leads to a change of slight axis orientation direction of LC molecules and appearance of various defects in the LC aligned structures. The technological ways to increase the aligning layer durability under influence of external factors were proposed.